Dermatoses in international travellers seen at Bordeaux teaching hospital travel clinic, 2015–2018: a GeoSentinel‐based study. (17th February 2020) - Blaizot, R.; Ouattara, E.; Receveur, M. C.; Mechain, M.; Pistone, T.; Malvy, D.; Duvignaud, A.
Summary: Skin disorders are frequent in travellers, but data vary between different studies. The objectives of the current study were to describe imported dermatoses in the Bordeaux GeoSentinel prospective database between August 2015 and March 2018. During the study period, 1025 travellers were seen in the clinic, 201 of them with dermatoses. Patients with skin disorders were more likely to be aged > 60 years (OR = 1.88, 95% CI 1.22–2.89), to be tourists (OR 3.04, 95% CI 2.03–4.55) and to have travelled to South America (OR = 2.18, 95% CI 1.29–3.67), and less likely to have sought pretravel advice (OR = 0.53, 95% CI 0.31–0.91). Skin bacterial infections (19.4%) and Zika virus infections (18.4%) were the most common dermatoses. Dengue fever and bacterial skin infections were the leading causes of hospitalization. The contribution of tropical diseases to imported dermatoses remains important. Lack of pretravel advice puts tourists at risk of significant diseases such as dengue fever, Zika virus and bacterial infections.